Advanced Time-Correlated Single Photon Counting Applications - Becker, Wolfgang (Springer Series in Chemical Physics, 2015)
This book is an attempt to bridge the gap between the instrumental principles of multi-dimensional time-correlated single photon counting (TCSPC) and typical applications of the technique. Written by an originator of the technique and by sucessful users, it covers the basic principles of the technique, its interaction with optical imaging methods and its application to a wide range of experimental tasks in life sciences and clinical research. The book is recommended for all users of time-resolved detection techniques in biology, bio-chemistry, spectroscopy of live systems, live cell microscopy, clinical imaging, spectroscopy of single molecules, and other applications that require the detection of low-level light signals at single-photon sensitivity and picosecond time resolution.